Effect of Mathematics Language Approach On Students Interest In Statistics In Senior Secondary Schools In Abuja Municipal Area Council - A. O, Agbo-Egwu,; Joseph, Joseph Ugochukwu (International Journal for Educational and Vocational Studies, 2020)
This study examined the effect of mathematics language on students interest in statistics in senior secondary school. The study employed quasi-experimental design of non-randomized pretest posttest control group type. Two research questions and two hypotheses guided the study. The sample of this study consisted of 250 Senior Secondary Two (SS2) students chosen out of the target population of 1250 students in all the 10-government grant aided secondary schools in Abuja Municipal Area Council. The sample comprised 125 male and 125 female students.  In each of the four sampled secondary schools, intact classes were used. Two sets of lesson plans on the topics under study were developed for the experimental and control groups respectively. Data were collected using Statistics Interest Inventory (SII). Research questions were answered using means and standard deviations while T-test was used to test the hypotheses at 0.05 alpha level of significance. The reliability coefficient is 0.88. From the research work, it was found out that the mathematical language when properly used improves students interest in Statistics and that gender has no significance difference in achievement. The study recommends among others that mathematics teachers should use the mathematical language instruction in teaching Statistics and other topics in mathematics to enhance students interest.